ANALISIS TINGKAT KESUBURAN TANAH PADA BERBAGAI PENGGUNAAN LAHAN DI KECAMATAN PUJON - Athalla Naufal R.S; Purwadi Purwadi; Purnomo Edi Sasangko (Fakultas Pertanian, Universitas Janabadra, 2023)
The level of land criticality in the Pujon sub-district area reaches a critical potential of 7.37% and very critical of 5.54%. This can be seen from the continued impact of the existence of critical land, namely landslides and floods in the Pujon area, causing the disconnection of access to the Malang - Kediri route. The occurrence of natural disasters in the Pujon sub-district area will cause the originally productive land to decline and if this tendency is allowed to continue it will allow a decrease in soil fertility status, therefore to suppress the decline in soil productivity / fertility it is necessary to analyze the level of soil fertility on agricultural land in Pujon sub-district. The assessment of soil fertility status in Pujon District is classified as medium to low soil fertility level. Land with low fertility dominates Pujon District to a large extent. The medium soil fertility rate is 7303.30 ha or 66.32% and the low soil fertility rate is only 33.68% of the area of 3708.38 ha located in a small part of Pujon sub-district. The texture of topsoil and subsoil soils in various land uses in the Pujon District area is sandy clay and clayey clay. Soil texture is an important factor that affects the physical, chemical, biological properties of the soil. Midifier K is found in land units T2, K2, K3, H3, Midifier KH is found in land units T3 and H2, Midifier K (Slope) is found in land units T4 (21%), K4 (24%), K (23%). Efforts needed to increase soil fertility are by fertilizing to increase the N content, controlling erosion and maintaining soil pH to increase the K content, applying lime to the soil to increase the pH, and making bench terraces to overcome slopes.intisariTingkat kekritisan lahan di wilayah kecamatan pujon mencapai potensial kritis sebesar 7.37% dan sangat kritis sebesar 5.54%. Hal ini dapat dilihat dari dampak lanjutan dari adanya lahan kritis yaitu terjadinya longsor dan banjir di wilayah Pujon sehingga menyebabkan terputusnya akses jalur Malang – Kediri. Terjadinya bencana alam di wilayah kecamatan pujon akan menyebabkan lahan yang semula produktif menjadi menurun dan jika kecenderungan ini dibiarkan secara terus menerus akan memungkinkan terjadinya penurunan status kesuburan tanah, Oleh karena itu untuk menekan menurunnya produktivitas / kesuburan tanah diperlukan Analisis Tingkat Kesuburan Tanah Pada Lahan Pertanian Dikecamatan Pujon. Penilaian status kesuburan tanah di wilayah Kecamatan pujon tergolong dalam tingkat kesuburan tanah sedang hingga rendah. Tanah dengan tingkat kesuburan rendah mendominasi Kecamatan Pujon seluas. Tingkat kesuburan tanah sedang seluas 7303,30 ha atau 66,32% dan tingkat kesuburan tanah rendah hanya 33,68% dari luas wilayah yaitu 3708,38 ha yang terletak di sebagian kecil wilayah kecamatan Pujon. Tekstur tanah topsoil dan subsoil pada berbagai penggunaan lahan di wilayah Kecamatan Pujon merupakan Lempung berpasir dan lempung berliat. Tekstur tanah merupakan faktor penting yang berpengaruh pada sifat fisik, kimia, biologi tanah. Midifier K terdapat pada satuan lahan T2, K2, K3, H3, Midifier KH terdapat pada satuan lahan T3 dan H2, Midifier K(Slope) terdapat pada satuan lahan T4 (21%), K4 (24%), K (23%). Upaya yang diperlukan untuk meningkatkan kesuburan tanah yaitu dengan pemupukan untuk meningkatkan kandungan N, pengendalian erosi dan mempertahankan pH tanah untuk meningkatkan kandungan K, pemberian kapur pada tanah untuk meningkatkan pH, dan membuat teras bangku untuk mengatasi kemiringan lereng.